Mechanisms of reactions of flavin mononucleotide triplet with aromatic amino acids. - Tsentalovich, Y; Lopez, J; Hore, P; Sagdeev, R (2002)
Chemical reactions between the photoexcited triplet state of flavin mononucleotide and the aromatic amino acids, N-acetyl tryptophan (TrpH), N-acetyl tyrosine (TyrOH), and N-acetyl histidine (HisH) in aqueous solution have been studied in the pH range 2-12. Across the whole pH range, the principal mechanism of reaction of both TrpH and TyrOH is shown to be electron transfer. For HisH, the mechanism and rate of the reaction depend on the protonation state of the reactants. In acidic conditions (pH < 4), reaction does not occur. At 4 < pH < 11, the reaction proceeds via hydrogen atom abstraction with a rate constant varying from 3.0 x 10(6) to 2.5 x 10(8) M(-1) s(-1). In extremely basic solution (pH > 12) the mechanism switches to electron transfer.